GAGASAN SEKOLAH BERTARAF INTERNASIONAL YANG RESPONSIF HAK KONSTITUSIONAL PENDIDIKAN - Mulyanto, Mulyanto (Fakultas Hukum Universitas Sebelas Maret, 2013)
The research aims to create a model for the implementation of Rintisan Sekolah Bertaraf Internasional (RSBI) that is responsive to the constitutional right to education. This study uses empirical descriptive qualitative research approach. Surakarta school research location. The results showed that: the First, Discrimination to get a quality education. RSBI School Students who dominated a wealthy family. The majority of schools are not able to meet the obligations RSBI 20% quota of poor students as well as the provisions of Article 16 paragraph (2) Permendiknas Number 78 of 2009. Second, the idea of ââorganizing models that are responsive RSBI constitutional rights education by: (1) Remove RSBI labeling for labeling lead to discrimination and discrimination is a violation of human rights, (2) Design of free primary education primary education as the mandate of Article 31 paragraph (2) of the 1945 Constitution and Article 26 paragraph (1) UDHR, and (3) Improving the quality of education for all schools without exception in particular improving the competence of teachers and educational facilities.